Crystal structure of mupirocin form I, C26H44O9. Issue 2 (8th April 2016) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of mupirocin Form I has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Mupirocin Form I crystallizes in space group P 21 (#4) with a = 12.562 81(16), b = 5.103 63(4), c = 21.713 34(29) Å, β = 100.932(1)°, V = 1366.91(2) Å 3, and Z = 2. Although the three hydroxyl groups and the carboxylic acid participate in a three-dimensional hydrogen bond network, the crystal energy appears to be dominated by van der Waals interactions. The Rietveld-refined and density functional optimized structures differ significantly. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File ™ .